Microwave-assisted pyrolysis of sewage sludge: A review - Zaker, Ali; Chen, Zhi; Wang, Xiaolei; Zhang, Qiang (Fuel processing technology, 2019)
Microwave-assisted pyrolysis is considered a promising technique for the thermochemical conversion of solid waste such as sewage sludge to useful energy products, including bio-char, bio-oil and bio-gas. However, a limited number of reports are found on the fundamentals and application of this process to extend the high potential of microwave-assisted pyrolysis of sewage sludge. This article presents up-to-date knowledge regarding important aspects of sewage sludge microwave pyrolysis, starting with the pretreatment of sewage sludge and the latest studies of conventional and microwave pyrolysis heating. This article further explores the products generated by microwave-assisted pyrolysis for sewage sludge including composition and yield. For instance, recent progress in experimental studies of both the catalytic and non-catalytic microwave-assisted pyrolysis of sewage sludge are reviewed and their results are analyzed in comparison to the product distributions resulting from non-microwave heating methods. Finally, this review discusses both the advantages and challenges of sewage sludge pyrolysis using microwave heating and the milestones that are necessary to be obtained in the future. •Sewage sludge characteristic has been discussed in details.•Products of microwave-assisted pyrolysis have been extensively analyzed.•A thorough review of catalytic and non-catalytic pyrolysis of sewage sludge•Catalysts showed a good performance for improving sludge-to-fuel conversion.•Microwave and conventional heating pyrolysis of sewage sludge are compared.